L-Asparaginase Production by Erwinia aroideae - Peterson, R. E. (Appl Microbiol, 1969)
Maximum yields of 1,250 IU (international unit)/g (dry weight of cells) of L-asparaginase were obtained in 8 hr from Erwinia aroideae NRRL B-138. Partial purification and concentration of the extracted L-asparaginase yielded a preparation with an activity of 275 IU/ml. Only one L-asparaginase was present as determined by electrophoresis, and the enzyme exhibited a pH optimum of 7.5 and a K(m) of 3 × 10(-3) M.